2002
DOI: 10.1086/338127
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Spectra of Type Ib Supernovae

Abstract: Synthetic spectra generated with the parameterized supernova synthetic-spectrum code SYNOW are compared to photospheric-phase spectra of Type Ib supernovae (SNe Ib). Although the synthetic spectra are based on many simplifying approximations, including spherical symmetry, they account well for the observed spectra. Our sample of SNe Ib obeys a tight relation between the velocity at the photosphere, as determined from the Fe II features, and the time relative to that of maximum light. From this we infer that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
252
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(285 citation statements)
references
References 35 publications
32
252
1
Order By: Relevance
“…In both Type IIb and Ib SNe, the metal and helium emission lines are significantly broader than in Type IIP SNe, as there is little or no hydrogen in the ejecta to take up the explosion energy. Type IIb and Type Ib SNe have similar light curves and spectral evolution (Woosley et al 1994;Filippenko et al 1994), a similarity further strengthened by evidence of trace hydrogen in many Type Ib SNe (Branch et al 2002;Elmhamdi et al 2006).…”
Section: Introductionmentioning
confidence: 75%
“…In both Type IIb and Ib SNe, the metal and helium emission lines are significantly broader than in Type IIP SNe, as there is little or no hydrogen in the ejecta to take up the explosion energy. Type IIb and Type Ib SNe have similar light curves and spectral evolution (Woosley et al 1994;Filippenko et al 1994), a similarity further strengthened by evidence of trace hydrogen in many Type Ib SNe (Branch et al 2002;Elmhamdi et al 2006).…”
Section: Introductionmentioning
confidence: 75%
“…The velocity increased slowly with time, reaching ∼ 7, 000 km s −1 (Fig. 3), an unusual behavior for SN Ib (see, e.g., Branch et al 2002). On the contrary, the velocities of the Fe lines declined with time.…”
Section: Light Curve Modelsmentioning
confidence: 83%
“…Benetti et al (2000) classified SN 2000H a type IIb supernova because of the hydrogen lines observed in the spectrum. However, these hydrogen lines were not obvious and the light curve showed more resemblance with a SN Ib (Branch et al 2002). Therefore, this supernova has been classified by other authors as a type Ib supernova (Branch et al 2002;Elmhamdi et al 2006).…”
Section: Sn 1996cbmentioning
confidence: 85%